Question about Vivendi Excel@ Mathematics Study Skills (71101) for PC, Mac

Ad

Hii,you can use the following solution
x^3 - 4x^2-12x=0
x(x^2-4x-12)=0
replacing -4x from -6x+2x
x(x^2-6x+2x-12)=0

Now Factoring
x(x(x-6) +2(x-6))=0
x(x-6)(x+2)=0
Solution is
x=0, x-6=0,x+2=0
1) x=0
2) x-6=0
=>x=6
3) x+2=0
=>x=-2

Posted on Jun 14, 2010

Ad

Hi,

a 6ya Technician can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repair professionals here in the US.

click here to Talk to a Technician (only for users in the US for now) and get all the help you need.

Goodluck!

Posted on Jan 02, 2017

Ad

I think of a balanced scale in my mind when I start these questions. What ever I do to one side, I have to do to the other side to keep it balanced. It starts balanced and I have to keep it balanced.

-(7-4x)=9

(-1) (-1)(7-4x) = 9 (-1) multiply both sides by -1 to get rid of the negative sign

7-4x=-9

7-4x-7=-9-7 subtract 7 from both sides

-4x = -16

-4x = -16

----- ----- divide both sides by -4 to get x by itself

-4 -4

x=4

Check by putting our answer in the original equation and see if the left side is equal to the right side.

Left Side Right Side

-(7-4(4)) 9

-(7-16)

-(-9)

9

Left side = right side

-(7-4x)=9

(-1) (-1)(7-4x) = 9 (-1) multiply both sides by -1 to get rid of the negative sign

7-4x=-9

7-4x-7=-9-7 subtract 7 from both sides

-4x = -16

-4x = -16

----- ----- divide both sides by -4 to get x by itself

-4 -4

x=4

Check by putting our answer in the original equation and see if the left side is equal to the right side.

Left Side Right Side

-(7-4(4)) 9

-(7-16)

-(-9)

9

Left side = right side

Mar 16, 2015 | Office Equipment & Supplies

if you mean {7(2)2+[(3-2)-4x(3)]2} or 7(2)2+[(3-2)-4x(3)]2

{28+[(1)-12]2}

{28+[-12]2}

{28+-24}

=4

or if it was 4x not 4 times

{7(2)2+[(3-2)-4x(3)]2}

28+[(1)-12x]2

28+-24x

=-28x+28

{28+[(1)-12]2}

{28+[-12]2}

{28+-24}

=4

or if it was 4x not 4 times

{7(2)2+[(3-2)-4x(3)]2}

28+[(1)-12x]2

28+-24x

=-28x+28

Jun 12, 2013 | Office Equipment & Supplies

See captured image below

Mar 01, 2011 | Office Equipment & Supplies

=>2x+3=0 ; taken x as common and 4-2=2 i.e. x(4-2) = 2x

=>2x=-3 ; +3's moved on the right-hand side, so it becomes -3

=>x=-3/2 ; 2 has been moved to the right-hand side and divided with -3 i.e 1/2 multiplied by -3 = -3/2

Good luck.

Thanks for using

Aug 13, 2010 | SoftMath Algebrator - Algebra Homework...

Let X=Number of pennies

Then (52-x) =Number of nickels.

You can then say that:

(x*1) + (52-x)(5) = 120

x + 260 - 5x = 120

260 - 4x = 120

260 - 4x + 4x = 120 + 4x

260 = 120 + 4x

260 - 120 = 120 + 4x - 120

140 = 4x

35 = x = Number of pennies

52 - 35 = 17 = Number of nickels

Verify: (35 * .01) + (17 * .05) = $1.20

.35 + .85 = $1.20

$1.20 = $1.20

Then (52-x) =Number of nickels.

You can then say that:

(x*1) + (52-x)(5) = 120

x + 260 - 5x = 120

260 - 4x = 120

260 - 4x + 4x = 120 + 4x

260 = 120 + 4x

260 - 120 = 120 + 4x - 120

140 = 4x

35 = x = Number of pennies

52 - 35 = 17 = Number of nickels

Verify: (35 * .01) + (17 * .05) = $1.20

.35 + .85 = $1.20

$1.20 = $1.20

Nov 15, 2009 | Microsoft Word 2003 for PC

Hello,

I am not lecturing you but I would rather you understand how to do the manipulations involved in isolating a variable.

You want to isolate y, Ok

Start stripping it of all that is not y.

3y + 4x =6. (Addition is commutative, I can change the order of addition)

The term with y is** added **to 4x. If I want the term in y alone on one side I perform the** inverse operation of addition**, a **substraction**. I subtract 4x from both sides.

3y+4x-4x=6-4x. But 4x-4x=0, and we are left with

**3y= - 4x+6**

This operation is sometimes summarized as make one term change side while changing its sign

It would do no harm to put the right side of the foregoing equation in parentheses. I do that to avoid errors)

3y= (-4x+6).

Now y is**multiplied** by the number 3. To isolate y I have to perform the **inverse operation** of the multiplication, namely the division by 3

3y/3 =(-4x+6)/3. The left hand side is just y

**y= (-4x+6)/3.**

While result is correct, I can also open the parentheses

y= -4x/3 +6/3

**y= -(4/3)*x +2.**

Hope it helps.

I am not lecturing you but I would rather you understand how to do the manipulations involved in isolating a variable.

You want to isolate y, Ok

Start stripping it of all that is not y.

3y + 4x =6. (Addition is commutative, I can change the order of addition)

The term with y is

3y+4x-4x=6-4x. But 4x-4x=0, and we are left with

This operation is sometimes summarized as make one term change side while changing its sign

It would do no harm to put the right side of the foregoing equation in parentheses. I do that to avoid errors)

3y= (-4x+6).

Now y is

3y/3 =(-4x+6)/3. The left hand side is just y

While result is correct, I can also open the parentheses

y= -4x/3 +6/3

Hope it helps.

Oct 22, 2009 | Texas Instruments TI-89 Calculator

Hello,

You have the method: apply it.

2 *(3x-4)(4x+5) =(6x-8)(4x+5)

Now apply the FOIL method

F: 6x*4x=24x^2

O: 6x*5=30x

I; -8*4x=-32x

L: -8*5=-40

so the result is

24x^2 + 30x-32x -40 =24x^2 -2x-40

You have the method: apply it.

2 *(3x-4)(4x+5) =(6x-8)(4x+5)

Now apply the FOIL method

F: 6x*4x=24x^2

O: 6x*5=30x

I; -8*4x=-32x

L: -8*5=-40

so the result is

24x^2 + 30x-32x -40 =24x^2 -2x-40

Oct 01, 2009 | The Learning Company Achieve! Math &...

6x+6=4x+12

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

sec^4X- sec^2X = 1/cot^4X + 1/cot^2X

RHS

1/cot^4X + 1/cot^2X

=1/(Cos^4X/Sin^4X) + 1/(Cos^2X/Sin^2X)

=Sin^4X/Cos^4X + Sin^2X/Cos^2X

=Sin^4X/Cos^4X + Cos^2X.Sin^2X/Cos^4X

=Sin^2X/Cos^4(Sin^2X + Cos^2X)

=Sin^2X/Cos^4X

=(1-Cos^2X)/Cos^4X

=1/Cos^4X - Cos^2X/Cos^4X

=1/Cos^4X - 1/Cos^2X

=Sec^4X - Sec^2X

=LHS

RHS

1/cot^4X + 1/cot^2X

=1/(Cos^4X/Sin^4X) + 1/(Cos^2X/Sin^2X)

=Sin^4X/Cos^4X + Sin^2X/Cos^2X

=Sin^4X/Cos^4X + Cos^2X.Sin^2X/Cos^4X

=Sin^2X/Cos^4(Sin^2X + Cos^2X)

=Sin^2X/Cos^4X

=(1-Cos^2X)/Cos^4X

=1/Cos^4X - Cos^2X/Cos^4X

=1/Cos^4X - 1/Cos^2X

=Sec^4X - Sec^2X

=LHS

Feb 02, 2009 | Super Tutor Trigonometry (ESDTRIG) for PC

[3(x-5)-4(-3x+2)]-[4(6-x)]

[(3x-15)-(12x+8)]-(24-4x)

(-9x-23)-(24-4x)

-13x-(-1)

this is 9th grade stuff.

[(3x-15)-(12x+8)]-(24-4x)

(-9x-23)-(24-4x)

-13x-(-1)

this is 9th grade stuff.

Sep 13, 2008 | Texas Instruments TI-84 Plus Calculator

Sep 19, 2010 | Vivendi Excel@ Mathematics Study Skills...

190 people viewed this question

Usually answered in minutes!

×